2018
DOI: 10.3390/nu10050606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Sugar Intake on Biomarkers of Subclinical Inflammation: A Systematic Review and Meta-Analysis of Intervention Studies

Abstract: It has been postulated that dietary sugar consumption contributes to increased inflammatory processes in humans, and that this may be specific to fructose (alone, in sucrose or in high-fructose corn syrup (HFCS)). Therefore, we conducted a meta-analysis and systematic literature review to evaluate the relevance of fructose, sucrose, HFCS, and glucose consumption for systemic levels of biomarkers of subclinical inflammation. MEDLINE, EMBASE, and Cochrane libraries were searched for controlled intervention studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 66 publications
1
58
0
5
Order By: Relevance
“…Overconsumption of fructose has been proposed as a risk factor for the metabolic syndrome, manifesting in dysfunctional adipose, liver, kidney, intestine and cardiovascular tissues [25]. One of the leading driving forces for the fructose-induced disturbances is the oxidative stress arising from an imbalance between the prooxidant and antioxidant systems [26]. This study demonstrated some favorable influences of probiotic supplementation with L. helveticus and L. plantarum on the metabolic parameters and renal antioxidant/ oxidant status of rats maintained on a high-fructose diet.…”
Section: Discussionmentioning
confidence: 99%
“…Overconsumption of fructose has been proposed as a risk factor for the metabolic syndrome, manifesting in dysfunctional adipose, liver, kidney, intestine and cardiovascular tissues [25]. One of the leading driving forces for the fructose-induced disturbances is the oxidative stress arising from an imbalance between the prooxidant and antioxidant systems [26]. This study demonstrated some favorable influences of probiotic supplementation with L. helveticus and L. plantarum on the metabolic parameters and renal antioxidant/ oxidant status of rats maintained on a high-fructose diet.…”
Section: Discussionmentioning
confidence: 99%
“…Since increased intake of fat and fructose is associated with systemic and tissue inflammation [14,15], we wanted to verify whether this response was elicited after our dietary treatment. To this end, we assessed markers of inflammation in plasma, e-WAT and brain areas.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Because this coating is intended for use in the oral environment, limiting the total amount of sucrose available to saccharolytic oral bacteria is an important consideration. Although sucrose alone has not been found to induce inflammation in gingival tissue, growth of saccharolytic bacteria on titanium surfaces has been shown to be enhanced by repeated exposure to high‐concentration sucrose solutions, and the resulting biofilms can have inflammatory effects on local tissue (Della Corte et al, ; Hert, Fisk, Rhee, & Brunt, ; Khan, Ansari, & Haqqi, ; Murakami, Mealey, Mariotti, & Chapple, ; Souza et al, ). The 1% sucrose solution was therefore selected for use in later experiments to improve the translatability of this coating by reducing total sucrose available to oral bacteria.…”
Section: Discussionmentioning
confidence: 99%